Increasing Cultural Literacy in Social Studies Learning Through an Inquiry Reflective Thinking Approach - Eka Yuliana Rahman; Aim Abdulkarim (JURNAL PENDIDIKAN IPS, 2024)
Cultural literacy is important in contemporary studies because it helps us understand and appreciate the cultural diversity that exists around us. In an increasingly connected and globalized world, understanding different cultures is key to promoting tolerance, reducing intercultural conflict, and building better relationships between people. Through cultural literacy in social studies learning using a reflective inquiry approach, we can understand the historical background, values, norms and traditions that form a culture. This research aims to explore through a literature review how to increase cultural literacy in social studies learning through reflective inquiry thinking. This research method uses a literature review by Cohen & Lawrence Manion, Keith Morrison. The results of cultural space research are formed by three axes, namely knowledge, values ​​and regulations. The influence of globalization has both negative and positive impacts on the existence of local culture and developing student competence through cultural literacy will develop awareness of the affective and cognitive dimensions of learning. Strengthening social studies content through a reflective inquiry thinking approach can be done with student-centered learning, diverse learning resources, and creating a conducive learning environment. Reflective inquiry is not only limited to statements or examinations, but includes the process of research, curiosity, analysis, and drawing conclusions about the things being examined or researched.